Assessing Impact to Infrastructures Due to Tephra Fallout From Öræfajökull Volcano (Iceland) by Using a Scenario-Based Approach and a Numerical Model - Barsotti, Sara; Di Rienzo, Dario Ingi; Thordarson, Thorvaldur; Björnsson, Bogi Brynjar; Karlsdóttir, Sigrún (Frontiers in Earth Science, 2018)
Mt. Öræfajökull is one of the most dangerous volcanoes in Iceland with potential for a VEI6 eruption and the generation of many severe associated hazards. It is not a frequently erupting volcano with two eruptions in the last 1100 years, in 1362 and 1727-28. During the 1362 eruption 10 km3 of freshly fallen tephra was emitted, the eruption plume reached the stratosphere and was dispersed offshore towards mainland Europe. In this study we investigate the possible impact due to tephra fallout to critical infrastructures in Iceland namely – roads, airports, electrical power-lines – in case of a new eruption at Öræfajökull of similar intensity as in 1362. The analysis is done by running several times the VOL-CALPUFF dispersal model to simulate the dispersal of ash in the atmosphere and its deposition on the ground. The resulting maps show the probability of exceeding critical thickness of the tephra fall. Critical infrastructures have been added to the analysis to get a quantitative assessment of the potential impact. The results indicate that in case of an event similar to the 1362 eruption, the tephra fallout could be expected over most of the country, with higher likelihood on the eastern side. The tephra fallout is likely to have a severe impact in the proximity of the volcano, generating a deposit with a load of up to 1000 kg/m2. The likelihood of failure for more than 160 km of the electrical power-line and for critical driving conditions on about 900 km of the main ring road is between 50-100%. The probability that the tephra fall will affect three of the main domestic airports is higher than 50%. An eruption of this magnitude is likely to affect commuting and communication between the greater Reykjavík area, where the government resides, and the rest of the country. Our analysis also reveals the limitations of current knowledge and understanding of the Öræfajökull volcano and highlights the need for further studies on past activity to better characterize its future behavior.